Purification and crystallization of a multimodular heterotrimeric complex containing both type I and type II cohesin–dockerin interactions from the cellulosome of Clostridium thermocellum - Currie, Mark A. (International Union of Crystallography, 2010)

(untitled)
The multimodular scaffoldin subunit CipA is the central component of the cellulosome, a multienzyme plant cell-wall-degrading complex, from Clostridium thermocellum. It captures secreted cellulases and hemicellulases and anchors the entire complex to the cell surface via high-affinity calcium-dependent interactions between cohesin and dockerin modules termed type I and type II interactions. The crystallization of a heterotrimeric complex comprising the type II cohesin module from the cell-surface protein SdbA, a trimodular C-terminal fragment of the scaffoldin CipA and the type I dockerin module from the CelD cellulase is reported. The crystals belonged to space group P2(1)2(1)2(1), with unit-cell parameters a = 119.37, b = 186.31, c = 191.17 Å. The crystals diffracted to 2.7 Å resolution with four or eight molecules of the ternary protein complex in the asymmetric unit.